2013
DOI: 10.1002/cam4.171
|View full text |Cite
|
Sign up to set email alerts
|

HPV DNAtesting improvesCIN2+ risk stratification and detection ofCIN2+ in delayed triage ofASCUSandLSIL. A population‐based follow‐up study fromWesternNorway

Abstract: In Norway, Pap smears with atypical squamous cells of uncertain significance (ASCUS) and low-grade squamous intraepithelial lesions (LSIL) are triaged after 6 months. The aim of the study was to evaluate effects of implementing human papillomavirus (HPV) test (2005) in delayed triage of ASCUS and LSIL in a cohort of women from Western Norway. After a survey of 119,469 cervical Pap smears during 2005–2007, a total of 1055 women with an index ASCUS or LSIL were included in the study and followed up for 3–6 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 43 publications
2
13
0
1
Order By: Relevance
“…Based on these criteria 1,262 women were selected from of 201,104 evaluated cytological smears. It should be noted that the outcome of HPV positivity and negativity in the first control after ASCUS/LSIL has been reported on previously in a partly overlapping cohort (2005–2007) of our study . For the 2006–2007 cohort, covering about half of the women in our study, 410 women (45.9%) tested positive and 484 (54.1%) tested negative at their first follow‐up of ASCUS/LSIL at baseline.…”
Section: Methodssupporting
confidence: 76%
See 1 more Smart Citation
“…Based on these criteria 1,262 women were selected from of 201,104 evaluated cytological smears. It should be noted that the outcome of HPV positivity and negativity in the first control after ASCUS/LSIL has been reported on previously in a partly overlapping cohort (2005–2007) of our study . For the 2006–2007 cohort, covering about half of the women in our study, 410 women (45.9%) tested positive and 484 (54.1%) tested negative at their first follow‐up of ASCUS/LSIL at baseline.…”
Section: Methodssupporting
confidence: 76%
“…In all these analyses the Pearson's χ 2 test was used to evaluate associations between categorical variables. Also, the progression risk of hr HPV‐negative women in a similar screening population cohort, were included for comparison. For some parameters mean ± standard error of the mean (SEM), median and progression risk with ±95% confidence intervals (CIs) were determined.…”
Section: Methodsmentioning
confidence: 99%
“…The ability to predict the risk of disease progression to HSIL would result in the improved management of ASC‐US/LSIL, with fewer patients being exposed to unnecessary colposcopic examinations or tissue biopsies. Recent studies have shown that human papillomavirus (HPV) infection is helpful in the risk stratification of lesions of CIN2 or higher . Likewise, the use of biomarkers to predict the progression of ASC‐US/LSIL could assist with triage care.…”
Section: Introductionmentioning
confidence: 99%
“…More specified classification of ASCUS cytology, such as ASCUS-reactive, ASCUS-LGSIL etc., might permit the optimal diagnostic and therapeutic management [1] . Furthermore, implementation of HPV-DNA testing in the follow-up of ASCUS cytology may contribute to the earlier diagnosis of HGSIL cases [20] .…”
Section: Discussionmentioning
confidence: 99%